Metabolic diversity in apple germplasm. Issue 2 (17th December 2013) - Khan, Sabaz A.; Tikunov, Yury; Chibon, Pierre‐Yves; Maliepaard, Chris; Beekwilder, Jules; Jacobsen, Evert; Schouten, Henk J.; Flachowsky, H.
Abstract We analysed metabolic diversity in apples from wild species, elite material and a F1 population, using liquid chromatography–mass spectrometry (LC‐QTOF‐MS). The evaluated elite material appeared to have strongly reduced levels of phenolic compounds, down to 1% of the concentrations in the investigated wild germplasm. In one quarter of the F1 population, the concentrations of phenolic compounds such as quercetin derivatives, procyanidin, catechin and epicatechin were further significantly reduced, due to accumulation of recessive alleles of putatively leucoanthocyanidin reductase, a structural gene that is located at the top of LG16. In another part of F1 progeny, putatively glycosylated forms of β‐glycols were up to 50 times more abundant compared to both parents. These metabolites were mapped with high logarithm of odds (LOD) scores at the top of LG8, and progeny that was homozygous recessive for the candidate gene showed the elevated levels. We hypothesize that this was caused by inheritance of non‐functional alleles of enoyl‐CoA hydratase gene. Both examples of transgressive segregation, where some progeny significantly deviated from both parents, were caused by accumulation of recessive alleles.